Multimorbidity in Acute Coronary Syndrome - Batty, Jonathan A.; del Toro, Tamara; Drayton, Daniel J.; Booth, Eleanor; Anik, Evrim; Sturley, Charlotte; Brown, Benjamin C.; Kearney, Mark T.; Hall, Marlous (JACC. Advances (Online), 2025)
Multimorbidity (the presence of multiple long-term conditions) increases the complexity of management decisions for patients presenting with acute coronary syndrome (ACS). The purpose of this study was to ascertain the prevalence of multimorbidity in ACS and assess its impact on clinical management and outcomes. Medline, Web of Science, Embase, and Cochrane were searched to July 2024 for studies that reported: 1) the prevalence of multimorbidity in patients with incident ACS or 2) ACS management and/or clinical outcomes, stratified by multimorbidity status. Random-effects meta-analysis was performed to calculate pooled summary statistics and was supported by narrative synthesis. Overall, 41 studies were included. Those at low risk of bias (23 studies; npooled = 9,227,657) demonstrated a pooled prevalence of multimorbidity of 46.6% (95% CI: 38.9%-54.2%). Study-level determinants of prevalence included study setting (high-income: 48.5% [40.5%-56.5%] vs low- to middle-income countries: 35.3 [30.5%-40.3%]); P = 0.006) and the number of conditions in the per-study definition of multimorbidity (R2 = 79.6%; P < 0.001). Individual-level determinants of multimorbidity included advanced age, non–ST-segment elevation presentation, previous cardiac procedures, and greater body mass index. Multimorbidity was associated with reduced usage of invasive management and secondary preventative medication. Multimorbidity was associated with short-term mortality (≤30 day; relative risk [RR]pooled 95% CI: 1.43 [95% CI: 1.14-1.78]; P < 0.01) and longer-term mortality (>30 day; RRpooled: 1.87 [95% CI: 1.51-2.32]; P < 0.01). Each additional pre-existing long-term condition was associated with a 16% excess risk of mortality (RRpooled: 1.16 [95% CI: 1.06-1.26]; P < 0.01). Multimorbidity is common, associated with reduced use of guideline-directed therapies and adverse clinical outcomes in patients with ACS. (The prevalence of multimorbidity and its impact on clinical outcomes in patients with acute myocardial infarction: a systematic review and meta-analysis; CRD42023447122) [Display omitted]